Traços da história de vida de três espécies de peixes importantes para a pesca na bacia do Rio Cuiabá, Mato Grosso - Silva, Evelyn Barzotto da (2018)
Reproduction represents one of the most important aspects of the biology of a species, since its success depends on the recruitment and, consequently, the maintenance of viable populations. Another important trait of life is growth, the estimation of these parameters is an indispensable item for calculating mortality and evaluating fishery resources. Therefore, growth and reproduction are complementary processes, reproduction contributes to the maintenance of the population compensating for the loss by mortality, while growth controls mortality and reproduction rates. Fishing in the Cuiabá River basin region is mainly concentrated in migratory species such as pintado (Pseudoplatystoma corruscans), cachara (Pseudoplatystoma reticulatum) and dourado (Salminus brasiliensis), as they are considered noble, at the best prices for professionals and represent a trophy for amateurs. Therefore, studies aiming to obtain more information about life cycle events, such as reproduction and growth, are essential for conservation, guiding management measures, management and preservation of the species in the Cuiabá river basin, filling gaps that still exist, especially when it is an important species for fishing and there is evidence of a reduction in their populations.